2007
DOI: 10.1080/13880200701389409
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity ofSilphium perfoliatum. Extracts

Abstract: Methanol and hexane extracts obtained from above-and below-ground organs of the cup plant Silphium perfoliatum L. (Asteraceae) were analyzed by gas chromatography-mass spectrometry (GC-MS). Eighty-five components were identified in the extracts. Moreover, evaluation of the content of total secondary metabolites (flavonoids, o-dihydroxyphenols, and glycoside-bonded oleanolic acid) was made in the methanol extract. It was found that leaf, inflorescence, and rhizome extracts of S. perfoliatum were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…Silphium perfoliatum L. is a perennial, tall, yellow flowering C 3 plant, characterized by a wide range of valuable practical traits and has been cultivated as a medical, melliferous, fodder, ornamental, and reclamation plant (Niqueux, 1981;Neumerkel and Märtin, 1982;Troxler and Daccord, 1982;Daniel and Rompf, 1994;Kowalski and Wolski, 2005;Kowalski and Kędzia, 2007;Zhang et al, 2010). In recent years, S. perfoliatum L. has been of interest as an energy crop, especially for biogas production (Vetter et al, 2010;Bauböck et al, 2014;Mast et al, 2014;Gansberger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Silphium perfoliatum L. is a perennial, tall, yellow flowering C 3 plant, characterized by a wide range of valuable practical traits and has been cultivated as a medical, melliferous, fodder, ornamental, and reclamation plant (Niqueux, 1981;Neumerkel and Märtin, 1982;Troxler and Daccord, 1982;Daniel and Rompf, 1994;Kowalski and Wolski, 2005;Kowalski and Kędzia, 2007;Zhang et al, 2010). In recent years, S. perfoliatum L. has been of interest as an energy crop, especially for biogas production (Vetter et al, 2010;Bauböck et al, 2014;Mast et al, 2014;Gansberger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The min imu m bactericidal activity (MBC) of the extract for different bacteria ranged between 0.312 to 1.25 mg/ ml, Methanol and Hexane extracts were more active than other extracts. This may be attributed to the presence of soluble phenolic and polyphenolic compounds [16] . The inhibitory effect of the ext ract of Elytraria Acaulis against pathogenic bacterial strains can introduce the plant as a potential candidate for drug development for the treatment of ailments caused by these pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, reported that the presence of some secondary metabolites in the root extract of Jatropha curcas inhibited some microorganism isolated from sexually transmitted infections [31]. This may be attributed to the presence of soluble phenolic and polyphenolic compounds [32].…”
Section: Discussionmentioning
confidence: 99%